Evolving role of skin sparing mastectomy - Kasem, Abdul (Baishideng Publishing Group Co., Limited, 2014)
Skin sparing mastectomy (SSM) can facilitate immediate breast reconstruction and is associated with an excellent aesthetic result. The procedure is safe in selected cases; including invasive tumours < 5 cm, multi-centric tumours, ductal carcinoma in situ and for risk-reduction surgery. Inflammatory breast cancers and tumours with extensive involvement of the skin represent contra-indications to SSM due to an unacceptable risk of local recurrence. Prior breast irradiation or the need for post-mastectomy radiotherapy do not preclude SSM, however the aesthetic outcome may be compromised. Preservation of the nipple areola complex is safe for peripherally located node negative tumours. An intraoperative frozen section protocol for the retro-areolar tissue should be considered in these cases. The advent of acellular tissue matrix systems has enhanced the scope of implant-based immediate reconstruction following SSM. Cell-assisted fat transfer is emerging as a promising technique to optimise the aesthetic outcome.